Reconsidering the Abuse That Dare Not Speak Its Name: A Criticism of Recent Legal Scholarship Regarding Same-Gender Domestic Violence - Lilith, Ryiah (2001)
This article argues that while recent legal scholarship effectively disputes the applicability of a gendered model of domestic violence to same-gender abuse, it goes too far in embracing a completely gender-neutral model. Part I explains the theoretical problems with the non-gendered model of domestic violence by examining in detail the research which is most often cited in legal writings in support of this model. Part II briefly explores the pragmatic implications for lesbian and gay male victims of domestic violence when law enforcement policies such as mandatory arrest are based on a model of domestic violence which ignores contexts such as gender. Finally, Part III recommends initially abandoning any single model of domestic violence that assumes a priori gender neutrality, and instead constructing multiple models limited to specific contexts and dynamics. Once these multiple models have been adequately assessed and tested, their common threads can be identified and woven into an integrated meta-model